Phosphate functionalized activated carbon as an efficient metal-free electrocatalyst for the oxygen reduction reaction. (14th September 2015) - Zhao, Shunyan; Li, Chuanxi; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract : Phosphate functionalized activated carbon as a metal-free electrocatalyst exhibits excellent electrocatalytic activity for the oxygen reduction reaction in an alkaline medium. Abstract : We demonstrate the fabrication of phosphate functionalized activated carbon by a facile heating method, as a metal-free electrocatalyst, which exhibits excellent electrocatalytic activity for the oxygen reduction reaction in an alkaline medium, it also enhances the durability and tolerance for methanol crossover effects. The improvement of the oxygen reduction reaction activity was closely related to the large specific surface area (976.4 m 2 g −1 ) and high phosphorus content (1.88%) of the electrocatalyst. The newly-developed material represents a promising step towards replacing Pt/C catalysts and could potentially lead to commercial-scale fuel cell production.